Genetic Insights Into Frailty: Association of 9p21-23 Locus With Frailty - Sathyan, Sanish; Barzilai, Nir; Atzmon, Gil; Milman, Sofiya; Ayers, Emmeline; Verghese, Joe (Frontiers in Medicine, 2018)
Frailty is a complex aging phenotype associated with increased vulnerability to disability and death. Understanding the biological antecedents of frailty may provide clues to healthy aging. The Genome Wide Association study (GWAS) hotspot, 9p21-23 region is a risk locus for a number of age-related complex disorders associated with frailty. Hence, we conducted an association study to examine whether variations in 9p21-23 locus plays a role in the pathogenesis of frailty in 637 community-dwelling Ashkenazi Jewish adults aged 65 and older enrolled in the LonGenity study. The strongest association with frailty (adjusted for age and gender) was found with the SNP rs518054 (Odds Ratio (OR): 1.635, 95%CI = 1.241-2.154; p value: 4.81 ×10-04) intergenic and located between LOC105375977 and C9orf146. The prevalence of four SNPs (rs1324192, rs7019262, rs518054 and rs571221) risk alleles haplotype in this region was significantly higher (compared to other haplotypes) in frail older adults compared to non-frail older adults (29.7% vs. 20.8%, p = 0.0005, respectively). Functional analyses using in-silico approaches placed rs518054 in the CTCF binding site as well as DNase hypersensitive region. Further, rs518054 was found to be in an enhancer site of NFIB gene located downstream. NFIB is a transcription factor that promotes cell differentiation during development, has anti-apoptotic effect, maintain stem cell populations in adult tissues and also act as epigenetic regulators. Our study found novel association of SNPS in the regulatory region in the 9p21-23 region with the frailty phenotype; signifying the importance of this locus in aging.